NEGOTIATING CRITICAL LITERACY IN JUNIOR HIGH: A TEACHER’S EXPLORATION USING FAIRY TALES - Nita Novianti (Indonesian EFL Journal, 2024)
Critical literacy is context dependent in nature; its practice is negotiated by teachers with their local contexts (Alford & Jetnikoff, 2016; Comber & Simpson, 2001). While this context dependency has been widely acknowledged, not much research has explored how teachers negotiate their local contexts to integrate critical literacy in their English classroom. Using the Framework for critical literacy negotiations in EFL classrooms (Novianti, 2023), action research involving a junior high school teacher was conducted. As part of the teacher’s professional learning program, the teacher negotiated the practice of critical literacy in her classroom. The results show that integrating critical literacy into the English classroom is a complex process requiring the teacher to negotiate multiple factors in their teaching practice as well as their knowledge and beliefs regarding literacy. The teacher’s main concern was negotiating a space for critical literacy in the existing curriculum, making sure the topic raised was relevant to students’ lived experiences, and considering local artifacts and happenings that could be raised in the instruction. Negotiation also occurs when the teacher integrated the principles of critical literacy pedagogy into her classroom teaching and learning, which comprise text analysis and critique, bridging the word and the world, and taking social action. The findings highlight the nature of critical literacy practice that is dependent upon teacher’s local contexts.